2017
DOI: 10.1364/oe.25.022575
|View full text |Cite
|
Sign up to set email alerts
|

Radiance based method for accurate determination of volume scattering parameters using GPU-accelerated Monte Carlo

Abstract: Volume scattering is an important effect in different fields, ranging from biology to lighting. Models for volume scattering usually rely on parameters that are estimated with inverse methods that iteratively fit simulations to experimental data. To obtain accurate estimates for these parameters, the scattered intensity distribution can be used in such fitting methods. However, it has been shown that for samples with long optical path lengths this type of data may result in poor parameter estimates. In this wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Alternatively, we can use a more complete measurement of the scattered spectral radiance. Studies have shown that the fitting accuracy is usually better if a more complete measurement of the scattered light is used [LLA∗13, CHCM17]. So fitting to a measured BSSRDF, a measured spectral radiance distribution, or multiple camera images [GZB∗13, HLC18] will provide more accurate results than fitting to radiant intensity or only total transmission/reflection.…”
Section: Inverse Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Alternatively, we can use a more complete measurement of the scattered spectral radiance. Studies have shown that the fitting accuracy is usually better if a more complete measurement of the scattered light is used [LLA∗13, CHCM17]. So fitting to a measured BSSRDF, a measured spectral radiance distribution, or multiple camera images [GZB∗13, HLC18] will provide more accurate results than fitting to radiant intensity or only total transmission/reflection.…”
Section: Inverse Methodsmentioning
confidence: 99%
“…Objective functions based on calculating a norm between measurements and simulations are also found in practice, especially for inverse adding‐doubling methods [PvGW93, LMD∗14]. Other types of objective functions which focus on minimizing the differences between the shape of the simulated and measured scattered distributions have also been described, using the normalized cross‐correlation [LLA∗13, CCL∗16] or the cosine distance [CHCM17]. Similarly, when using measurements that can include a significant amount of variance or are very dense, it can be useful to define the objective function so that it minimizes the difference of aggregate data such as a histogram of the measured and simulated distributions [YX16].…”
Section: Inverse Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Monte Carlo simulations have been used, for example, in studying photoacoustics [31,32], fluorescence tomography [33,34], time resolved diffuse spectroscopy [35,36], statistical models for photon transport [37], biophotonics of corals [38], dose optimization for photodynamic therapy [39] and laser treatment of port-wine stains [40]. Furthermore, the first studies in which Monte Carlo is utilised in the solution of the inverse problem of an optical imaging problem have been implemented [15,[41][42][43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%